2009
DOI: 10.1088/0004-637x/708/2/1388
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Energy Dependence of the Relation Between Optical and X-Ray Emission in Quasars

Abstract: We develop a new approach to the well-studied anti-correlation between the optical-to-X-ray spectral index, α ox , and the monochromatic optical luminosity, l opt . By cross-correlating the SDSS DR5 quasar catalog with the XMM-Newton archive, we create a sample of 327 quasars with X-ray S/N > 6, where both optical and X-ray spectra are available. This allows α ox to be defined at arbitrary frequencies, rather than the standard 2500Å and 2 keV. We find that while the choice of optical wavelength does not strong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
94
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 55 publications
11
94
1
Order By: Relevance
“…Indeed, it is lower than those found by Strateva et al (2005, e.g.) (0.14) and by Young et al (2010) (0.16), but slightly higher than that evaluated by Gibson et al (2008) (0.10). Values found in previous simultaneous studies are also of the same order, e.g.…”
Section: Dispersioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Indeed, it is lower than those found by Strateva et al (2005, e.g.) (0.14) and by Young et al (2010) (0.16), but slightly higher than that evaluated by Gibson et al (2008) (0.10). Values found in previous simultaneous studies are also of the same order, e.g.…”
Section: Dispersioncontrasting
confidence: 57%
“…For example, both Lusso et al (2010) and G10 found evidence of a decrease of α ox with Eddington ratio. Moreover, Young et al (2010) found a significant partial anti-correlation with the Eddington ratio when the dependence on L UV is accounted for; the significance increases if the X-ray energy in the α ox definition is increased.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The non-linear relationship between L X and L UV (parameterised as log L X = γ log L UV + β) has been found in both optically and X-ray selected AGN samples and exhibits a slope γ around 0.5 − 0.7 (Vignali et al 2003;Strateva et al 2005;Steffen et al 2006;Just et al 2007;Green et al 2009;Lusso et al 2010;Young et al 2010;Marchese et al 2012;Jin et al 2012), implying that optically bright AGN emit relatively less X-rays than optically faint AGN. Such relation is independent of redshift, it is very tight (∼ 0.2 dex observed dispersion, Lusso & Risaliti 2016), and it has also been employed as a distance indicator to estimate cosmological parameters such as Ω M and Ω Λ .…”
Section: Introductionmentioning
confidence: 99%
“…see Young et al 2010;Vasudevan & Fabian 2009;Grupe et al 2010;Lusso et al 2012, and references therein). To this end, statistically complete and well-defined samples of AGNs equipped with X-ray spectral data and with a reliable estimate of the accretion parameters (SMBH mass, the absolute accretion rate, the accretion rate normalized to the Eddington limit) are required.…”
Section: Introductionmentioning
confidence: 99%